Sport Chaplains and Social Workers: A Theoretical Understanding of a Necessary Component of an Interprofessional Collaborative Practice in Sport in the United States - Lauren Beasley PhD, MS, LMSW; Emily J Johnson MPH, MS; Steven N. Waller PhD, DMin, CSPC (Movement and Being: The Journal of the Christian Society for Kinesiology, Leisure and Sports Studies, 2022)
Holistic care of athletes is a growing area of research and practice. Yet, there is still much to consider as attention to this matter continues to expand. Specifically, what are the different theoretical perspectives of each profession working together towards the holistic care of athletes? The theoretical understanding between professions is essential for effective interprofessional teams—what some scholars have termed interprofessional cultural competence. The purpose of this paper is thus to provide the theoretical underpinnings for collaboration between sport chaplains and social workers, both emerging professions within interprofessional care in sport. This paper presents the unique partnership of sport chaplains and social workers in the spiritual care of athletes. Furthermore, it seeks to clarify the theoretical foundations of each profession, and how then these professions can then work together most effectively. Suggestions and ethical considerations are also given for best practices in the execution of this collaboration.
Keywords: holism; ecological systems theory; interprofessional teams; spiritual care